Optical design and study of a wireless IV drip detection device - Tseng, Wei-Hsiung; Juan, Diana; Hsiao, Wei-Cheng; Chan, Cheng-Han; Wang, Kuang-Ching; Ma, Hsin-Yi; Lee, Hsiao-Yi (Microelectronics and reliability, 2019)
During the treatment process, intravenous infusion therapy is a common medical treatment for many inpatients. However, patients may experience side effects that increase the hours of care and interfere with their families' work and sleep. During the infusion, the nursing staff have to control the flow rate, monitor the emptying of the drop bottle (drip bag) and pay attention to the possibility of an obstruction which are activities that increase their workload. In this study, the wireless intravenous (IV) drip injection detection device is equipped with an infrared induction magnetic buckle group on the sleeve of the intravenous infusion in order to monitor the infusion flow rate and reduce the risk of a complication. The device has many features such as light weight, high portability, simple operation, and reusability. This study involved the design of a photovoltaic system that automatically detects the level of an IV drop bottle or drip bag. The system mainly includes an LED light source, a sensing module for detecting light passing through the drop bottle, and a biconvex focusing lens (BFL) for concentrating light to enhance the intravenous drip injection detection device's signal. Therefore, in this study, wireless IV drip injection detection device was designed, evaluated and analyzed. The system also uses a built-in database to analyze the difference between coloured drops and blood to improve the reliability of the IV drip detection assembly. When the light sensing module detects the liquid in the drop bottle (drip bag), the receiver sends a signal; if the bottle (bag) is empty, the light sensing module activates the wireless transmitter and the wireless transmitter warns the caregiver via the wireless transmission mode. In the future, cooperation between manufacturers and clinical trials will help to stabilize the cost, thereby improving the quality of intravenous infusion care and reducing the workload on nursing staff.